Identification of core microbiota in the fermented grains of a Chinese strong-flavor liquor from Sichuan. (15th March 2022) - Jiao, Wenjing; Xie, Fei; Gao, Lei; Du, Liquan; Wei, Yanxia; Zhou, Jian; He, Guiqiang
Abstract: In traditional fermentation process of Chinese strong-flavor liquor, composition, dynamic succession, and interaction of microbial community in the fermented grains (FG) are fluctuant, resulting in instability and inconsistency of liquor flavor and quality. It is therefore important to reveal the core microbiota of FG from different pit ages and layers of fermentation cellars in this study. Firstly, Venn analysis showed that 14 and 13 ubiquitous bacterial and fungal genera were respectively observed. Meanwhile, Lactobacillus, Aquabacterium, Thermoactinomyces, Aspergillus, Thermoascus, Kazachstania, Pichia, and Rhizomucor with a relative abundance over 1% in all samples were identified as dominant microbiota. Additionally, 8 bacterial and 3 fungal genera were significantly correlated with flavor compounds including esters, alcohols, acids, and aldehydes by RDA, indicating these genera were flavor-associated microbiota. Furthermore, co-occurrence network analysis demonstrated that 7 bacterial and 5 fungal genera were highly connected with other genera, which were defined as co-occurring microbiota. Taken together, Lactobacillus, Thermoactinomyces, Aquabacterium, Aspergillus, and Kazachstania were identified as the core microbiota in Chinese strong-flavor liquor brewing process. Core microbiota of liquor brewing microecosystem were defined in this work, it is of paramount important to construct synthetic microbiota for stable and homogenous production of high-quality liquor. Highlights: Microbiota of FG from different ages and layers of fermentation pit was revealed. Ubiquitous, dominant, flavor-associated, and co-occurring genera were identified. Core microbiota included Lactobacillus, Thermoactinomyces, Aquabacterium, Kazachstania and Aspergillus.